Metodologias de ensino/aprendizagem de língua portuguesa como L2 para surdos - Gomes, Anderson Spier (2014)
This paper aims to analyze didactic material concerning the teaching of Portuguese as a second language to deaf students investigating the concepts of deaf individuals/students, language, grammar/text and bilingualism that underlies the material as also the relationship between the theory basing the teacher's manual and the choice of texts, aiming at contributing with the work and discussions in the area. With the purpose of thoroughly observe the methodologies of Portuguese teaching to deaf students the theoretical basis of this research lies in the most up to date line of studies in the Portuguese teaching-learning process, such as Marcuschi (2013), Kock (2013), Perini (2007) and also Bakhtin (2010) and Vygotsky (2010), focusing on the matters of language conceptions and on the discussions involving grammar and bilingualism that are covered in the analyzed materials. In summary, the analysis of such materials show lack of socially run texts and demonstrate that there is still a field to be explored by researchers in the area of Portuguese teaching as a foreign language, specially to deaf students.